Mendelian randomization study on the relationship between fibroblast growth factors and their receptors and the risk of spontaneous abortion - LI Jing; SUN Caixuan; LI Ao; XUE Yilu; WANG Runlin; TANG Yuyun; CAO Yuanyuan (Yixue xinzhi zazhi, 2025)
Objective To investigate the causal relationship between fibroblast growth factors (FGFs), their receptors (FGFRs) and spontaneous abortion (SA). Methods FGFs, FGFRs, and SA related GWAS data were obtained from the FinnGen Alliance and Genome-wide Association Studies Databases. Using MR analysis method to explore the causal relationship between FGFs, FGFRs and SA, with the inverse-variance weighted method (IVW) as the main analysis method. Sensitivity analysis was conducted using MR-PRESSO, MR Egger, Cochran's Q, and the leave-one-out method. Results A total of 22 exposure factors were selected. The IVW results showed that FGF22 increased the risk of SA [OR=1.099, 95%CI (1.001, 1.206), P=0.047], while FGF12 decreased the risk of SA [OR=0.858, 95%CI (0.774, 0.951), P=0.003]. There were no significant causal associations between other FGFs, FGFRs, and SA. Sensitivity analysis conducted on the causal association between FGF12, FGF22, and SA showed that Cochran's Q test (P>0.05) indicated no heterogeneity, MR Egger test (P>0.05) indicated no horizontal pleiotropy, MR-PRESSO method did not detect outliers and no SNPs that had a significant impact on the results were detected using leave-one-out method. Conclusion FGF12 is a protective factor for SA, while FGF22 is a risk factor for SA. The result provide potential molecular markers for early prediction and targeted intervention of SA.